Adverbial attachment and anaphoric relations cannot access an emotive predicate in exclamatives, unlike in emotive assertions, which argues against a silent emotive matrix predicate. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Adverbial attachment and anaphoric relations cannot access an emotive predicate in exclamatives, unlike in emotive assertions, which argues against a silent emotive matrix predicate.
iso-id: iso:argument:HgzNuf9t; sha256: sha256:8020b0dc70ddab8a6c270138647ca6336ede90df17776bae737a4eea806310d0